Creep model for natural fiber polymer composites (NFPCs) based on variable order fractional derivatives: Simulation and parameter study. Issue 24 (24th December 2019) - Xiang, Guangjian; Yin, Deshun; Meng, Ruifan; Lu, Siyu
ABSTRACT: To describe the creep behavior of natural fiber/polymer composites (NFPCs), a novel variable fractional order creep model is proposed in this work. With experimental data of polymer composites obtained from creep tests at different temperatures and with different fiber content, the effectiveness of the proposed model has been demonstrated. With the advantage of only four parameters, the variable order creep model is proved to give accurate descriptions on the creep behaviors of polymer composites by comparing simulated results with experimental data. Furthermore, a parameter study is conducted, which reveals the physical significance of model parameters. It is observed that the order increases linearly with time, which demonstrates the polymer composites softened during creep. Analysis of order indicates that high temperatures can activate the softening of the materials and the variable order is able to depict the change of microstructures of polymer composites. Besides, the relations between fiber content and order curves provide new perspectives on manufacturing NFPCs. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48796. Abstract :